It's Not Just the Taking Part that Counts: 'Like Me' Perceptions Connect the Wider Public to Minipublics. Issue 2 (14th October 2020) - Pow, James; van Dijk, Lisa; Marien, Sofie
Many deliberative democrats herald the potential of minipublics to help improve the quality of democratic decision-making. Yet these democratic innovations present a paradox: how can the use of minipublics be perceived as legitimate by the maxi-public when most citizens cannot participate? In this article, we address this question in the context of Lafont's argument that minipublics amount to 'shortcuts' in the democratic process. We challenge this argument by hypothesising that non-participants perceive minipublics to be legitimate when they perceive minipublic participants to be like them – and when they perceive politicians to be unlike them. Similarly, we expect that the relative importance of descriptive similarity will be related to the issue in question. We test our hypotheses in the deeply divided context of Northern Ireland, where a minipublic was held on the salient and contentious question of the polity's constitutional future. Survey evidence confirms that 'like me' perceptions constitute a significant predictor of minipublic legitimacy perceptions. Our results have implications for the communication of minipublic features to the broader public, for the use of minipublics alongside conventional decision-making processes, and for further empirical research.